THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE AND BEHAVIOR OF BREASTFEEDING AND INTAKE OF COMPLEMENTARY FEEDING WITH NUTRITIONAL STATUS OF CHILDREN AGED 6-24 MONTHS AT KESUNEAN HEALTH CENTER CIREBON - Mauli Ardhiya; Ignatius Hapsoro; Shofa Nur Fauzah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The insufficient nutrient intake in the certain time may affect physical growth and development of children. The percentage of babies with exclusive breast feeding are only 37.3%. It is still under the national target. This research aims to examine the correlation of knowledge, attitude, and behavior of breastfeeding and intake of complementary feeding with nutritional status in 6-24 months old children at kesunean health center in Cirebon.Methodology: This study was a cross-sectional research conducted in Kesunean Health Center Cirebon City. Totaling 100 mothers of children aged 6 to 24 months was selected by consecutive sampling. The nutritional status was calculated based on weight of age whereas the predictors (knowledge, attitude, behavior) was asked by 31 questions. The statistical analysis used Spearman test.Results: The univariate result showed that more than a half of children’s mothers was in aged 26 to 35 years and 48% graduated from senior high school. Additionally, 63% of the children had a good nutritional status. The bivariate analysis found that knowledge (p=0.001 and r=0.561), attitude (p=0.001 and r=0.498), and behavior (p=0.001 and r=0.606) had a correlation with nutritional status.Conclusions: Knowledge, attitude, and behavior of mother had correlation with nutritional status. Public health center should promote the importance of breastmilk and provide the counseling to the mother. Keywords: Breastfeeding, intake of complementary feeding, nutritional status of children.